Profile of cancer patients attending a tertiary care center - Antoney Unni Xavier; Amgiasvasanth AM (International Journal of Medical Research and Review, 2020)
Introduction: In India, around 555,000 people died of cancer in the year 2010. Cancer is a major cause of morbidity and mortality in developing and developed countries. In many low-income and middle-income countries, including India, most of the population does not have access to a well organized and well-regulated cancer care system.Objective: (1) To study the socio-demographic profile of cancer patients attending tertiary care center.(2) To study the type, site and at what stage cancers are being reported to tertiary care center (3) To study the association of the cancer type with socio-demographic variables.Material and methods: A Hospital-based Cross-Sectional Study carried out from November 2013 to October 2014. Detailed pre-designed and pre-tested proforma is used to collect information on the socio-demographic profile. All diagnosed cancer patients admitted at SDM College of Medical Sciences and Hospital. A total of 381 were studied during the study period.Results: Total of the 381 cancer patients, Males were 154 (40.4%) and females were 227 (59.6%), it was found that majority of male, 78 (50.6%) study subjects were in the age group of 60-69 years, in socioeconomic status male subjects were in lower-middle and upper lower class i.e. 40 (26%) female were in upper-middle-class i.e. 70 (30.8%), according to the present study breast cancer (21.3%) was most prevalent, followed by CA liver and biliary tract (14.7%), followed by lungs (8.7%). the male was diagnosed in stage III of disease accounting 67(43.5%) female patients were diagnosed in stage II 86 (37.9).Conclusion: Breast cancer more common among younger age group and upper SES, Cervical cancer more common among lower SES, Lung cancer in literates’. Liver cancer more common among the older age group and lower SES. So, these groups can be targeted for health education and screening for early diagnosis and treatment.